PORTFOLIOS ASSESSMENT AS A METHOD OF ASSESSMENT OF LANGUAGE IN ESL CLASSROOM CONTEXT - Juella Rumiris (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2015)
The use of portfolios as an assessment tool probably is unlikely common in Asian countries. Portfolios is commonly considered as a compilation of students’ work for a certain period of time. In fact, the portfolios may show the originality of and the nature of students’ learning improvement. In this paper, the writer will discuss portfolios as a method of assessment in English as Second Language or English as Foreign Language (ESL/EFL) classroom context from teacher’s perspective. This paper is designed with this format order: firstly to explain about the degree of portfolios method to assess content, skills and knowledge in the teach-ing-learning program in the ESL/EFL context, to correlate portfolios system to model of curriculum planning and policy context. Secondly, to discuss the strengths and weaknesses of portfolios method from a theoretical perspective, and analyse the validity, reliability, and fairness. Thirdly, to specify the association of portfolios method and the types of assessment and the correlation of portfolios method with assessment for learning. Fourthly, to evaluate the degree of portfolios method of assessment promoting learning of the knowledge, skills, and abilities related to my teaching experience.Keywords : Portfolios, Assessment, Curriculum, Learning, Knowledge, Skills.